Polycistronic Expression System for Pichia pastoris Composed of Chitino- and Chitosanolytic Enzymes - Kaczmarek, Michal B.; Struszczyk-Swita, Katarzyna; Xiao, Meng; Szczęsna-Antczak, Mirosława; Antczak, Tadeusz; Gierszewska, Magdalena; Steinbüchel, Alexander; Daroch, Maurycy (Frontiers in Bioengineering and Biotechnology, 2021)
Chitin is one of the most abundant biopolymers. Due to its recalcitrant nature and insolubility in accessible solvents, it is often considered waste and not a bioresource. The products of chitin modification such as chitosan and chitooligosaccharides are highly sought, but their preparation is a challenging process, typically performed with thermochemical methods that lack specificities and generate hazardous waste. Enzymatic treatment is a promising alternative to these methods, but the preparation of multiple biocatalysts is costly. In this manuscript, we biochemically characterised chitin deacetylases of Mucor circinelloides IBT-83 and utilised one of them for the construction of the first eukaryotic, polycistronic expression system employing self-processing 2A sequences. The three chitin-processing enzymes; chitin deacetylase of M. circinelloides IBT-83, chitinase from Thermomyces lanuginosus, and chitosanase from Aspergillus fumigatus were expressed under the control of the same promoter in methylotrophic yeast Pichia pastoris and characterised for their synergistic action towards their respective substrates.